2014
DOI: 10.1007/s00265-014-1830-8
|View full text |Cite
|
Sign up to set email alerts
|

Group composition, relatedness, and dispersal in the cooperatively breeding cichlid Neolamprologus obscurus

Abstract: Cooperative breeding has been studied intensively in many species of birds and mammals but remain less well studied in fish. We report a remarkable new example of a cooperatively breeding cichlid from Lake Tanganyika, Neolamprologus obscurus. Using field observations and microsatellite DNA analyses, we studied group structure, helping behavior, relatedness, and dispersal of this species. We present four major observations. First, large territorial breeding males mated with one to eight breeding females, each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(82 citation statements)
references
References 60 publications
2
79
1
Order By: Relevance
“…Subordinate males in a closely related species ( Neolamprologus obscurus ) seem to adopt this strategy: they disperse from the territory of their mother, but remain within the larger territory of their father (Tanaka et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Subordinate males in a closely related species ( Neolamprologus obscurus ) seem to adopt this strategy: they disperse from the territory of their mother, but remain within the larger territory of their father (Tanaka et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…), they may wait to disperse from their father's territory until they reach a size at which they may be able to challenge for a dominant breeding position in another group or can opportunistically disperse to a vacant territory (Tanaka et al . ). Subordinates in the closely related N. obscurus appear to adopt similar strategies—subordinate females disperse away from their father's territory at a smaller size, but subordinate males remain in their father's territory, likely because subordinate males are more tolerated in the territory of their father than a territory of an unrelated male (Tanaka et al .…”
Section: Discussionmentioning
confidence: 97%
“…Comparing N. pulcher 's genetic architecture of social behaviours to those of other closely related cichlid species that differ in their degree of sociality and cooperative breeding might shed light on the evolution of sociality within this lineage. For instance, the Lamprologini tribe of Lake Tanganyika cichlids comprises around one hundred species which range from nonsocial to highly social and represent a system in which cooperative breeding has evolved repeatedly (Dey et al., ; Heg & Bachar, ; Taborsky, ; Tanaka et al., ). Furthermore, comparisons of genetic correlations between social behaviours in other cooperatively breeding animals, for instance meerkats (Huchard et al., ), red squirrels (Taylor et al., ), yellow‐bellied marmots (Petelle et al., ) but also cooperatively breeding birds (Hunter, ; Komdeur, ) and insects (Leadbeater et al., ; Queller et al., ), could also reveal whether general patterns in cooperative breeders exist, which would contribute to better understand how cooperative breeding evolves.…”
Section: Discussionmentioning
confidence: 99%
“…The multi-male/multi-female category described in Heg and Bachar (2006), which has been referred to by Tanaka et al (2018), denotes groups consisting of multiple sexually mature males and females. To what extent these adult subordinates gain reproductive share is known from 6 cooperatively breeding cichlids for which genetic data are available (Neolamprologus pulcher, N. savoryi, N. obscurus, N. multifasciatus, Julidochromis ornatus, J. transcriptus;see Kohler, 1998;Awata, Munehara, & Kohda, 2005;Dierkes, Heg, Taborsky, Skubic, & Achmann, 2005;Kohda et al, 2009;Tanaka et al, 2015;Hellmann et al, 2016;Heg et al in revision; see Taborsky, 2009Taborsky, , 2016. Without exception, all these studies revealed that groups in the respective species contain larvae, young or helpers of different degrees of relatedness to the breeders, revealing that they are genetically non-monogamous.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, immigration, which occurs regularly in the cooperatively breeding cichlids investigated thus far (see Taborsky, 2016 for review), significantly reduces relatedness between helpers and beneficiaries. Consequently, in the cooperatively breeding cichlids for which genetic data are available, the mean within-group relatedness values are clearly below 0.5 (Awata et al, 2005;Dierkes et al, 2005;Kohler, 1998;Taborsky, 2009;Tanaka et al, 2015), varying with age and size of the subordinates (Dierkes et al, 2005). Dey et al (2019) state that the alternative phylogenetic trees presented in Tanaka et al (2018) also suggest 4-5 transitions to cooperative breeding.…”
Section: Introductionmentioning
confidence: 99%